2011
DOI: 10.1007/s12540-011-0823-7
|View full text |Cite
|
Sign up to set email alerts
|

Roll bonding behaviour of Al-3003/Al-4043 and Al-3003/Zn sheets

Abstract: In the present study, the roll bonding behaviour of Al-3003/Al-4043 and Al-3003/Zn sheets were compared. The bi-layer sheets were produced by a roll bonding process at different reductions in thickness and rolling temperatures. The joint strengths of the sheets were evaluated by peel and bend testing before and after supplemental annealing treatment. The peeled surfaces were examined using a scanning electron microscope. The results indicated that the Al-3003/Al-4043 sheets were bonded with higher joint streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 24 publications
(26 reference statements)
0
0
0
Order By: Relevance
“…The bonding of different aluminum alloys for braze-used products can be performed via the already mentioned hot rolling [12], where the bond criterion and its correlated parameters can be predicted. Movahedi et al [13] studied the roll bonding behavior of EN AW 3003 with EN AW 4043 and EN AW 3003 with a Zn sheet and concluded that the first-mentioned clad combination was bonded with higher joint strengths and lower threshold reductions in thickness compared to the second mentioned analyzed cladded combination. The evolution of the grain structure in both-sided clad EN AW 3003 with EN AW 4343 was investigated by Kim et al [14], but the comparison of corrosion resistance for cold-rolled and post-brazed material was not reported, and that is the novelty in this article.…”
Section: Introductionmentioning
confidence: 99%
“…The bonding of different aluminum alloys for braze-used products can be performed via the already mentioned hot rolling [12], where the bond criterion and its correlated parameters can be predicted. Movahedi et al [13] studied the roll bonding behavior of EN AW 3003 with EN AW 4043 and EN AW 3003 with a Zn sheet and concluded that the first-mentioned clad combination was bonded with higher joint strengths and lower threshold reductions in thickness compared to the second mentioned analyzed cladded combination. The evolution of the grain structure in both-sided clad EN AW 3003 with EN AW 4343 was investigated by Kim et al [14], but the comparison of corrosion resistance for cold-rolled and post-brazed material was not reported, and that is the novelty in this article.…”
Section: Introductionmentioning
confidence: 99%